Periapical tissue repair of dog teeth after intracanal administration of capsaicin 0.075% - Pavan, Nair Narumi Orita; Endo, Marcos Sergio; Bruder, Marina Viudes; Pavan, Angelo José; Grossmann, Eduardo; Hernandes, Luzmarina; Cuman, Roberto Kenji Nakamura (Brazilian Dental Science, 2015)
Objective: The aim of this study was make a descriptively evaluate the repair of the periapical region of dog teeth. Material and Methods: Thirty-six root canals were used,eighteen were filled with 0.075% capsaicin and calcium hydroxide (test paste)and the rest eighteen root canals were filled with calcium hydroxide (control group). Histological analyzes were performed to classify inflammation as absent, mild, moderate or severe. The analyses also classified the presence or absence of repairat 7, 14 and 30 days.Results: The use of 0.075% capsaicin did not modify the inflammatory response and repairwhen compared to control group. Conclusion: Our data suggests that test group with 0.075% capsaicin as intracanal administration could be indicated for tissue repair; furthermore other experiments should be carried out to evaluate possible clinical use of capsaicin for atypical odontalgia. Keywords: Capsaicin; Repair; Inflammation; Periapical tissue.